Digitalisation and flight: how can donors leverage digital technologies to support refugees? - Charles Martin-Shields (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Increasing global access to digital technologies is creating opportunities and challenges for donors and the humanitarian agencies with which they work to support people fleeing from war, massive human rights abuses and other emergencies. Digital tools make it easier for refugees to reach out to each other and humanitarian agencies, and can support greater efficiency in institutional efforts to provide essentials like medicine, food and money. However, the effective use of digital tools to support refugee processes comes with a set of challenges. The key question for donors is: What are the existing approaches to digitalisation in refugee response, and the lessons learned, that donors can use to inform how they support digitalisation in refugee processes? To address this question, there are three things donors should focus on when developing a digital strategy for supporting refugees: Donors must avoid the problem of “technology looking for a problem to solve”; knowing how refugee communities already use digital tools is the best way to avoid this. Generally, refugees themselves will have found innovative ways to meet their information needs, and donors can provide financial and technical assistance to support access to the existing technologies. Building digital tools from scratch is an option when there is no existing tool available to meet the needs of refugees or workers in the field. Custom tools are often best deployed at the organisational level for managing information or resources. Donors should look to innovation and technology hubs, such as the United Nations High Commissioner for Refugees' (UNHCR) Innovation Service, to organise partnerships between United Nations (UN) agencies, refugee-focused NGOs and technology firms. Donors must be realistic about what to expect from a digital solution. Technology can be useful, but it is not a silver bullet for solving every information management challenge. Ethics and safety issues must be central in the design of any digital intervention. Donors must take responsibility in making sure the partners they work with can meet the data protection and privacy standards outlined by the International Committee of the Red Cross's (ICRC) handbook on digital data protection. This policy brief provides a review of how refugees use digital tools, gives examples from organisations deploying digital technologies in the field, and discusses the effectiveness of and the ethical issues surrounding the use of digital technologies to support refugees. By putting the needs of refugees at the centre of their digital strategies and working with implementing organisations, such as UNHCR and Mercy Corps, to develop technology solutions that meet the needs of refugees and field staff safely and ethically, donors can get the most out of digital tools for supporting refugees.
Keywords: 330; Technologie und Innovation; Soziale Sicherung und Inklusion